Validation of a dedicated positron emission tomography scanner for imaging of the distal limb of standing horses. Issue 4 (21st February 2022) - Spriet, Mathieu; Edwards, Lisa; Arndt, Stefanie; Wilson, Sabrina S.; Galuppo, Larry D.; Stepanov, Pavel; Beylin, David
Abstract: A positron emission tomography (PET) scanner, with an openable ring of detectors, was specifically designed to image the distal limb of standing horses. The goals of this prospective, preclinical, experimental, methods comparison study were to validate the safety of the scanner, assess image quality, and optimize scanning protocols. Six research horses were imaged three times (twice standing, once anesthetized) and six horses in active race training were imaged once under standing sedation. Multiple scans of both front fetlocks were obtained with different scan durations and axial fields of view. A total of 94 fetlock scans were attempted and 90 provided images of diagnostic value. Radiotracer uptake was the main factor affecting image quality, while motion did not represent a major issue. Scan duration and field of view also affected image quality. Eight specific lesions were identified on PET images from anesthetized horses and were all also independently recognized on the PET images obtained on standing horses. Maximal standardized uptake values (SUVmax) had good repeatability for the assessment of specific lesions among different scans. Three feet and six carpi were also successfully imaged. This study validated the safety and practicality of a PET scanner specifically designed to image the distal limb in standing horses. Proper preparation of horses, similar to bone scintigraphy, is important for image quality. A 4‐min scan with 12 cm field of view was considered optimal for clinical fetlock imaging. Evaluation of a larger clinical population is the next step for further assessment of the clinical utility of PET imaging in horses.